2006
DOI: 10.2225/vol9-issue5-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of transferable multiple antibiotic resistance amongst coliform bacteria isolated from a treated sewage effluent in Antofagasta, Chile

Abstract: Antibiotic-resistant coliform bacteria from raw and treated water from activated sludge of a sewage treatment plant were isolated on eosin methylene blue agar (EMB) plates in the separate presence of ampicillin, tetracycline, chloramphenicol and streptomycin. Antibiotic resistant coliforms obtained from inflow and effluent waters were studied to determine influences of treatment on the species composition, resistance patterns and transferable resistance in these bacteria. The bacterial counts obtained showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…The disposal of treated sewage into rivers, lakes or elsewhere may or may not influence environmental bacterial populations (Sloan et al, 2014). Some studies have found that wastewater treatment can raise or lower the proportions of antibiotic resistant bacteria which carry antibiotic resistance plasmids (Silva et al, 2006). The observation of increased resistance frequency to ampicillin, tetracycline, streptomycin and chloramphenicol after wastewater treatment has previously been reported by Reinthaler et al (2013).…”
Section: Discussionmentioning
confidence: 81%
“…The disposal of treated sewage into rivers, lakes or elsewhere may or may not influence environmental bacterial populations (Sloan et al, 2014). Some studies have found that wastewater treatment can raise or lower the proportions of antibiotic resistant bacteria which carry antibiotic resistance plasmids (Silva et al, 2006). The observation of increased resistance frequency to ampicillin, tetracycline, streptomycin and chloramphenicol after wastewater treatment has previously been reported by Reinthaler et al (2013).…”
Section: Discussionmentioning
confidence: 81%
“…The same tendency was observed in case of erythromycin resistant bacteria, with the highest number in winter. The increase of the number of resistant bacteria could be caused by the higher usage of this antibiotic to treat bacteria diseases (Figure 1b), because as it was previously stated, the exposition to the drug can cause the increase of bacterial resistance (Silva et al 2006, Soufi et al 2010. Because erythromycin is known to possess wider bactericidal spectrum and it is used more often than sulfamethoxazole/trimethoprim, it is possible that its usage increased during winter.…”
Section: Discussionmentioning
confidence: 89%
“…Little is currently known about the dynamics of antibiotic-resistant bacteria and genes encoding antibiotic resistance in wastewater treatment plants (WWTPs). It has been speculated that the wastewater treatment process may increase the proportion of resistant bacteria in outlet (Silva et al, 2006).…”
Section: Introductionmentioning
confidence: 99%